Assessment of pedagogical challenges on soft skills training acquired among business education students - Abdulrazak Mohammed; Hadiza Nuhu Usman; Sakariyahu Shehu; Abdullahi AbdulRafiu (Journal of Management and Business Education)
The research work investigated on the assessment of pedagogical challenges on soft skills training acquired among business education students in Kwara State University, Malete and Al-Hikmah University, Ilorin. The researchers raised two research questions were raised, also two null hypotheses were formulated at 0.05 level of significance. The researchers adopted survey research design of descriptive type for the study. A total of 255 students studying Business Education from Kwara State University and Al-Hikmah University made up the population of the study. A Census population was adopted, the researchers used the entire population and there was no sample size and sampling technique. The research instruments were given to research experts from Ahmadu Bello University, Zaria for face and content validation of the research instrument. The researchers used self-developed instrument entitled ‘Soft Skills Training and Pedagogical Challenges Problems (SSTPCP)’. The researchers pilot tested the research instrument Ahmadu Bello University, Zaria using 20 Business Education students and Cronbach Alpha method was used to obtained the reliability co-efficient of 0.87. The researchers seek for consent of the department and the students before personally administering the instruments in the area of the study. The researchers use mean and standard deviation to answer the research questions raised for the study, while t-test was used to test the null hypotheses formulated at 0.05 level of significant. The study found, among other things, that poor attention spans, memory problems, and comprehension difficulties are some of the pedagogical barriers that keep students in business education from acquiring soft skills. It was suggested, based on the study's findings, that business education students try to think back on the abilities they have acquired as soon as they are taught by business educators.